Optimization design and experiment of Chinese cabbage (Brassica rapa pekinensis) groove-spoon type precision seed metering device based on discrete element method - Dun, Guoqiang; Ma, Chunyu; Zhang, Chaoxia; Ji, Xinxin; He, Yang (Frontiers in Mechanical Engineering, 2025)
Aiming at problems such as Chinese cabbage seeds’ small size, easy breakage, light quality, difficulty realizing single grain precision sowing, injury, and poor uniformity of seed discharge, a kind of groove-spoon type precision seed metering device with a guide ring combining a groove U-hole for Chinese cabbage was proposed. The seeding spoon features a tapered platform design, with a smaller upper section and a larger lower section. Preventing seed buildup during filling and enhancing single-seed sowing probability. It reduces seed damage caused by gravity-based seed clearance, incorporates seed guide rings and discharge channels to assist seed release, and improves seed distribution uniformity. The key structural parameters and working parameters of the seed metering device were determined through theoretical analysis, and the force analysis of cabbage seeds in filling, clearing, guiding, and casting was carried out. The discrete element single factor simulation test and quadratic regression orthogonal rotation combination test were conducted with U-hole diameter, U-hole depth, and inclination angle of the top of the seed scoop as test factors, and qualified rate, multiple rate and leakage rate as test indexes, the test results show that when the U-hole diameter is 2.32 mm, the U-hole depth is 1.76 mm. The inclination angle of the top of the seed spoon is 15.34°, and the seed metering device works optimally. Based on the simulation test, bench test, and field test under the optimal parameter combination, the results of the simulation test showed a qualified rate of 92.22%, a multiple rates of 4.21%, and a leakage rate of 3.57%; the qualified index of the bench test result 91.33%, the multiple indexes is 4.89%, and the leakage index is 3.78%, and the error value between the simulation and the bench test result is small, which proves the reliability of the simulation test; when the forward speed of the planter was 0.4–1.2 m/s, the qualified index of the field test was 89.90%, the multiple indexes was 6.06%, and the leakage index was 4.04%, which meets the planting requirements of Chinese cabbage precision direct seeding.